An Analysis of the HRGA Department Process - Teofilus Nugraha Setiadarma; Benedictus Rahardjo (Institute of Research and Community Outreach - Petra Christian University, 2020)
This study provided an analysis of HRGA Department processes at XYZ Company. The KPIs of the HRGA Department at XYZ Company has been ineffectively and inefficiently processed since 2017 till the first quartile of 2018. This study, therefore, aims to provide an analysis of the processes through the Recruitment, Training & Development, and Personnel Administration, with the fishbone diagram used to determine the main and root causes of the problems. The result showed that the processes were ineffective and inefficient because the company's working instruction partially complied, lacked employee leadership, and the organizational structure has not been updated in accordance with its development.